A photocatalysis-biological immobilization-sediment adsorption composite water purification material, a preparation method and application thereof
By designing a composite water purification material combining photocatalysis, biological fixation, and sediment adsorption, a tiered synergistic pollution control system was constructed, solving the problem of efficiency decay of photocatalysis and biological carriers under low-temperature conditions, and achieving synergistic removal and stable purification of pollutants during low-temperature periods.
Patent Information
- Application Number
- CN202611317028.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-11-03
AI Technical Summary
Existing photocatalysis-biological coupling technology suffers from performance degradation at low temperatures, reduced quantum efficiency of photocatalytic materials, and lack of low-temperature bacterial fixation in biological carriers, leading to decreased pollutant removal efficiency and water quality fluctuations.
A photocatalytic-biological immobilization-sediment adsorption composite water purification material is designed, comprising a sediment passivation-targeted adsorption layer, a cross-linked modified biological carrier layer, and a low-temperature responsive photocatalytic layer, which are fixedly connected by an isolation layer and a bonding layer. A tiered synergistic pollution control system is constructed by using a visible light responsive composite semiconductor photocatalyst and low-temperature acclimatized functional bacteria.
During the low-temperature period, the system achieves synergistic control of organic pollutants, nitrogen and phosphorus pollutants, and endogenous pollutants in the sediment, thereby improving pollution control performance and stability, mitigating the risk of water quality rebound, and realizing active synergistic purification of water and sediment.
Smart Images

Figure CN123026319A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment technology, specifically to a photocatalytic-biological immobilization-sediment adsorption composite water purification material, its preparation method, and its application. Background Technology
[0002] In northern and southern my country, water bodies typically experience a low-temperature period of 3-6 months (0-10℃) during winter. Conventional water purification technologies generally experience a sharp decline in effectiveness under these conditions, becoming an industry-wide challenge hindering the long-term purification of water bodies during this period. Currently, the mainstream technology in the field of low-temperature water purification is photocatalysis-biological coupling technology (ICPB).
[0003] The direct coupling system of photocatalysis and biodegradation is a core research hotspot. Its core design idea is to achieve functional partitioning through porous carriers, load photocatalysts on the outer surface of the carrier to contact water and light, and at the same time allow functional microbial membranes to attach to the internal pores of the carrier. This aims to combine the strong oxidizing ability of photocatalysis to recalcitrant organic matter with the biotransformation ability of microorganisms to nitrogen and phosphorus pollutants, thereby achieving the synergistic removal of multiple pollutants in water.
[0004] However, in existing technologies, the lack of low-temperature modification of photocatalytic materials easily leads to a sharp drop in quantum efficiency; the biological carriers lack low-temperature bacterial fixation technology, resulting in a significant decrease in bacterial activity and pollutant removal efficiency. Furthermore, photo-biological coupling systems are mostly single or two-layer structures, lacking sufficient synergy between water pollution reduction and sediment-based pollution control, which easily leads to decreased pollution control efficiency and water quality fluctuations during low-temperature periods. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a photocatalytic-biological immobilization-sediment adsorption composite water purification material, its preparation method, and its application. The photocatalytic-biological immobilization-sediment adsorption composite water purification material provided by this invention has good low-temperature adaptability, enabling a tiered synergistic pollution control system and active synergistic purification of water and sediment, thus helping to improve pollution control performance and stability at low temperatures.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a photocatalytic-biological immobilization-sediment adsorption composite water purification material, comprising, from bottom to top, a sediment passivation-targeted adsorption layer, a cross-linked modified biological carrier layer, and a low-temperature responsive photocatalytic layer; the layers are fixedly connected by an isolation layer and / or an adhesive layer. The sediment passivation-targeted adsorption layer includes a mineral adsorption material and a framework support material, wherein the mineral adsorption material is modified with rare earth elements and / or transition metal elements. The cross-linked modified biological carrier layer includes a cross-linked modified porous biological carrier and low-temperature functional bacteria immobilized in the porous biological carrier; The low-temperature responsive photocatalytic layer includes a visible light responsive composite semiconductor photocatalyst. The sediment passivation-targeted adsorption layer is in contact with the sediment, and the low-temperature responsive photocatalytic layer is oriented towards the overlying water and light.
[0007] Preferably, the mineral adsorbent material includes lanthanum-modified bentonite and zirconium-modified zeolite, wherein the mass ratio of lanthanum-modified bentonite to zirconium-modified zeolite is 1~2:1. The skeleton support material includes one or more of the following: quartz sand, volcanic rock particles, shale ceramsite, and zeolite coarse aggregate. The mass of the skeleton support material is 10-15% of the mass of the mineral adsorbent material.
[0008] Preferably, the sediment passivation-targeted adsorption layer further includes one or more of iron oxides, manganese oxides, and hydroxyapatite.
[0009] Preferably, the porous biological carrier includes one or more of polyurethane sponge, polypropylene fiber, activated carbon fiber, ceramsite, and porous ceramics; the porous biological carrier is granular or fibrous. The water contact angle of the porous biological carrier is 63~67°; The low-temperature functional bacteria include one or more of the following: cold-resistant nitrifying bacteria, cold-resistant denitrifying bacteria, and low-temperature phosphate-solubilizing bacteria.
[0010] Preferably, the visible light responsive composite semiconductor photocatalyst includes one of the following: g-C3N4 / BiVO4 composite catalyst, g-C3N4 / Bi2WO6 composite catalyst, TiO2 / BiVO4 composite catalyst, and g-C3N4 / ZnO composite catalyst.
[0011] Preferably, the thickness of the sediment passivation-targeted adsorption layer is 8-15 mm, the thickness of the cross-linked modified biological carrier layer is 5-10 mm, and the thickness of the low-temperature responsive photocatalytic layer is 2-5 mm; the layers are separated by non-woven fabric and fixed by needle punching composite process.
[0012] This invention provides a method for preparing the above-mentioned photocatalytic-biological immobilization-sediment adsorption composite water purification material, comprising the following steps: (1) Mix mineral adsorbent material modified with rare earth elements and / or transition metal elements, skeleton support material and inorganic binder, press and solidify them to obtain sediment passivation-targeted adsorption layer. (2) The porous biological carrier is subjected to argon plasma surface pre-activation treatment to obtain a surface-activated biological carrier; the surface-activated biological carrier is mixed with a grafting solution containing an amination reagent and subjected to an amination reaction to obtain an amination biological carrier; the amination biological carrier is immersed in glutaraldehyde solution and subjected to cross-linking treatment to obtain a cross-linked modified porous biological carrier. The low-temperature functional strains were subjected to low-temperature acclimatization to obtain low-temperature acclimatized functional bacteria; the cross-linked modified biological carrier was mixed and incubated with the low-temperature acclimatized functional bacteria, and the unfixed free bacterial cells were washed away and the residual aldehyde groups were blocked to obtain a porous biological carrier loaded with low-temperature functional bacteria; the porous biological carrier loaded with low-temperature functional bacteria was fixed on the surface of the sediment passivation-targeted adsorption layer to obtain a biological carrier layer. (3) The visible light responsive composite semiconductor photocatalyst is mixed with a binder and coated on the surface of the cross-linked modified biological carrier layer to obtain a low-temperature responsive photocatalytic layer; (4) The sediment passivation-targeted adsorption layer, the cross-linked modified biological carrier layer and the low-temperature responsive photocatalytic layer are sequentially composited and fixed from bottom to top to obtain a photocatalytic-biological fixation-sediment adsorption composite water purification material.
[0013] Preferably, in step (2), the discharge power of the argon plasma surface pre-activation treatment is 80~120W, the chamber pressure is 15~25Pa, and the treatment time is 3~8min; The amination reagent in the grafting solution containing the amination reagent includes one or more of aminopropyltriethoxysilane, aminopropyltrimethoxysilane, chitosan, and polyethyleneimine. The glutaraldehyde solution has a mass fraction of 0.1% to 0.5%, the crosslinking treatment temperature is 2 to 8°C, and the crosslinking treatment time is 0.5 to 2 hours. The low-temperature acclimatization includes: sequentially culturing the low-temperature functional strain suspension at 15℃ for 5-10 days, at 10℃ for 5-10 days, and at 5℃ for 10-20 days; During the mixed incubation, the OD600 of the low-temperature acclimatized functional bacteria is 0.5~0.7, the incubation temperature is 2~8℃, the incubation time is 2~5h, and the shaking speed is 80~120rpm.
[0014] Preferably, the density of the sediment passivation-targeted adsorption layer after pressing and molding in step (1) is 0.8~1.2 g / cm³. 3 ; In step (3), the mass of the binder is 5-8% of the mass of the visible light responsive composite semiconductor photocatalyst; after the visible light responsive composite semiconductor photocatalyst is mixed with the binder, the coating amount on the surface of the cross-linked modified biological carrier layer is 150-250 g / m². 2 .
[0015] This invention provides the application of the above-mentioned photocatalytic-biological fixation-sediment adsorption composite water purification material in the control of water pollution in low-temperature periods, wherein the temperature of the water in the low-temperature period is 0~10℃.
[0016] This invention provides a photocatalytic-biological immobilization-sediment adsorption composite water purification material, comprising, from bottom to top, a sediment passivation-targeted adsorption layer, a cross-linked modified biological carrier layer, and a low-temperature responsive photocatalytic layer. This invention addresses four major shortcomings of existing low-temperature water purification materials: poor low-temperature adaptability, limited functionality, lack of water-sediment synergy, and insufficient long-term effectiveness. It fundamentally solves these pain points through structural design and synergistic mechanisms of the water purification material, as detailed below: (1) A three-layer directional composite structure of "photocatalysis-biological fixation-sediment adsorption" is proposed to construct a tiered synergistic pollution control system of "photo-biological-adsorption". The present invention sets up a low-temperature responsive photocatalytic layer, a cross-linked modified biological carrier layer, and a sediment-targeted passivation adsorption layer from top to bottom. Each layer is isolated by non-woven fabric and fixed by a needle-punched composite process to form a mechanically stable and highly efficient mass transfer whole. Each layer has a clear division of labor and is hierarchically matched to construct a tiered reduction barrier for pollutants at the "water-biofilm-sediment" interface, realizing the synchronous synergistic treatment of multiple pollutants in both water and sediment phases in a single material. Based on the three-layer directional composite structure, pollutants can sequentially undergo surface photocatalytic transformation, middle layer biodegradation, and bottom layer adsorption and passivation fixation processes to form a tiered pollution control system facing the overlying water and sediment interface.
[0017] The composite material comprises a surface photocatalytic layer that converts some recalcitrant organic pollutants into relatively biodegradable intermediates, a middle biological immobilization layer that further converts organic and nitrogenous pollutants, and a sediment passivation-targeted adsorption layer that adsorbs, exchanges ions with, coordinates, or precipitates phosphates, ammonium nitrogen, and / or heavy metals released from the sediment. By reducing the competition of organic pollutants for adsorption sites on the bottom layer and reducing the release of endogenous pollutants from the sediment into the overlying water, the composite material of this invention helps maintain long-term pollution control performance. Preferably, by controlling the immobilization method and dosage of each functional component, the risk of release of photocatalytic components, metal-modified components, and binders into the water body can be reduced.
[0018] (2) A dual-path low-temperature adaptation design is adopted to improve the pollution control performance under low-temperature conditions. On the one hand, the present invention uses a visible light responsive composite semiconductor photocatalyst as a photocatalytic active material to improve the utilization of light energy under low-temperature conditions and promote the separation of photogenerated carriers and interfacial reactions; on the other hand, the present invention performs surface activation and cross-linking-assisted immobilization treatment on the biological carrier and loads low-temperature acclimatized functional bacteria to improve the retention stability of functional bacteria on the carrier surface under low-temperature conditions.
[0019] The photocatalytic layer, biological immobilization layer, and sediment passivation-targeted adsorption layer work synergistically to make the composite material suitable for the coordinated control of organic pollutants, nitrogen and phosphorus pollutants, and endogenous pollutants in sediment in water bodies at low temperatures of 0-10℃. Specifically, at 0-3℃, the pollution control effect of the composite material is mainly due to the physicochemical immobilization effect of the sediment passivation-targeted adsorption layer and the photochemical conversion effect of the photocatalytic layer; at 5-10℃, the pollutant conversion effect of the biological immobilization layer is further enhanced.
[0020] (3) Achieving active synergistic purification of water and sediment. This invention adopts a directional layout where the sediment adsorption layer adheres to the sediment and the photocatalytic layer faces the water. The upper and middle layers simultaneously purify water pollutants, while the bottom layer actively blocks the release of endogenous nitrogen, phosphorus, and heavy metals from the sediment through a triple mechanism of "physical barrier-chemical precipitation-ion exchange." The physical barrier is achieved by the overall framework of the sediment passivation adsorption layer; chemical precipitation and ion exchange rely on lanthanum-modified bentonite, zirconium-modified zeolite, and iron-manganese oxides. Unlike existing passive treatment modes, this invention can achieve simultaneous blocking of endogenous pollution and water purification, which helps to mitigate the risk of water quality rebound during low-temperature periods. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of a photocatalytic-biological immobilization-sediment adsorption composite water purification material. Detailed Implementation
[0022] This invention provides a photocatalytic-biological immobilization-sediment adsorption composite water purification material, comprising a sediment passivation-targeted adsorption layer, a cross-linked modified biological carrier layer, and a low-temperature responsive photocatalytic layer arranged sequentially from bottom to top; the layers are fixedly connected by an isolation layer and / or an adhesive layer. The sediment passivation-targeted adsorption layer includes a mineral adsorption material and a framework support material, wherein the mineral adsorption material is modified with rare earth elements and / or transition metal elements. The cross-linked modified biological carrier layer includes a cross-linked modified porous biological carrier and low-temperature functional bacteria immobilized in the porous biological carrier; The low-temperature responsive photocatalytic layer includes a visible light responsive composite semiconductor photocatalyst. The sediment passivation-targeted adsorption layer is in contact with the sediment, and the low-temperature responsive photocatalytic layer is oriented towards the overlying water and light.
[0023] In this invention, the bottom layer of the composite water purification material is a sediment passivation-targeted adsorption layer, comprising mineral adsorption materials and a framework support material. The mineral adsorption materials are modified with rare earth elements and / or transition metal elements. Preferably, the rare earth elements include lanthanum, and the transition metal elements preferably include zirconium. Specifically, the mineral adsorption materials preferably include lanthanum-modified bentonite and zirconium-modified zeolite. This invention selects a combination of lanthanum-modified bentonite and zirconium-modified zeolite as the core functional components of the bottom layer based on the following considerations: Lanthanum-modified bentonite has specific chemisorption capacity for phosphate, firmly fixing phosphorus by generating lanthanum phosphate precipitate; the passivation product has high stability in anoxic sediment environments and is not easily released secondary; zirconium-modified zeolite has dual functions of phosphorus and nitrogen control, removing phosphorus through ligand exchange while efficiently adsorbing ammonium ions through the cation exchange capacity of the zeolite framework. The combined use of these two materials can produce a synergistic effect, exhibiting superior adsorption performance compared to single-component modified materials. Furthermore, it can more comprehensively reduce the content of various forms of active phosphorus in sediment, achieving simultaneous treatment of phosphorus chemical precipitation passivation and ammonia nitrogen ion exchange retention. In this invention, the lanthanum doping amount in the lanthanum-modified bentonite is preferably 3%~6% of the dry weight of the bentonite, and the particle size of the lanthanum-modified bentonite is preferably ≥100 mesh, more preferably 100~200 mesh. The preparation method of the lanthanum-modified bentonite in this invention includes the following steps: Sodium-based bentonite is mixed with sulfuric acid solution and activated by acid to obtain acidified bentonite; The aqueous suspension of the acidified bentonite was mixed with a lanthanum source, and the pH was adjusted to 7.8-8.2 to carry out a lanthanum modification reaction, thereby obtaining lanthanum-modified bentonite.
[0024] In this invention, the mass fraction of the sulfuric acid solution is preferably 8-12%, more preferably 10%; the acid activation temperature is preferably room temperature, and the time is preferably 0.5-2 hours, more preferably 1 hour. The acid activation is preferably carried out under stirring conditions, and the stirring rate is preferably 150-250 rpm, more preferably 200 rpm. After acid activation, the resulting acid-activated product is preferably washed, subjected to solid-liquid separation, and the resulting solid is dried, ground, and sieved. In this invention, the washing is preferably done with water until the pH value is 7, the solid-liquid separation is preferably done by vacuum filtration, the drying temperature is preferably 80°C, the drying time is preferably 6 hours, and the sieving is preferably done through a 100-mesh sieve.
[0025] In this invention, the preferred ratio of acidified bentonite to water in the aqueous suspension of acidified bentonite is (2.5~4.0) g: 200 mL, more preferably (3.0~3.5) g: 200 mL. In this invention, the lanthanum source is preferably one or more of lanthanum chloride, lanthanum nitrate, and lanthanum sulfate, more preferably lanthanum chloride. In this invention, after mixing the aqueous suspension of acidified bentonite with the lanthanum source, the molar concentration of lanthanum ions in the resulting mixture is preferably 55~65 mmol / L, more preferably 60 mmol / L. In this invention, the mixing method is preferably a sequential process of ultrasonic dispersion and stirring. The ultrasonic dispersion power is preferably 150~250 W, more preferably 200 W, and the time is preferably 25~35 min, more preferably 30 min. The stirring temperature is preferably 48~52℃, more preferably 50℃, the stirring speed is preferably 150~250 rpm, more preferably 200 rpm, and the time is preferably 2~3 h, more preferably 2.4~2.6 h. After mixing, the pH value is adjusted to 7.8-8.2, preferably 8.0, and the reagent for adjusting the pH value is preferably a 1 mol / L sodium carbonate solution. In this invention, the temperature of the lanthanum modification reaction is preferably 48-52℃, more preferably 50℃, and the time is preferably 1.5-3 h, more preferably 2-2.5 h. Through the lanthanum modification reaction, this invention stably loads the lanthanum component onto the surface and interlayer of bentonite. After the lanthanum modification reaction, this invention preferably subjectes the obtained lanthanum modification reaction solution to sequential washing, drying, grinding, and sieving.
[0026] In this invention, the zirconium doping content in the zirconium-modified zeolite is preferably 4-6% of the dry basis weight of the zeolite, more preferably 5%; the particle size of the zirconium-modified zeolite is preferably ≥100 mesh, more preferably 100-200 mesh. In this invention, the preparation method of the zirconium-modified zeolite includes the following steps: A natural zeolite aqueous suspension was mixed with zirconium oxychloride, and the pH was adjusted to 9.8-10.2 to carry out a zirconium modification reaction, thus obtaining zirconium-modified zeolite.
[0027] In this invention, the preferred ratio of natural zeolite to water in the natural zeolite aqueous suspension is 100g:250mL. The preferred mass ratio of natural zeolite to zirconium oxychloride is (4-6):1, more preferably 5:1. After mixing, the pH value is adjusted to 9.8-10.2, preferably 10.0, and preferably using a 2mol / L sodium hydroxide solution. The preferred temperature for the zirconium modification reaction is room temperature, and the preferred time is 1.5-3.5h, more preferably 2h. After the zirconium modification reaction, the resulting zirconium modification reaction solution is preferably subjected to solid-liquid separation, and the resulting solid is washed, dried, pulverized, and sieved. The preferred washing is washing with water until neutral, the preferred drying temperature is 105℃, the preferred drying time is 12h, and the preferred sieving is passing through a 100-mesh sieve.
[0028] In this invention, the preferred mass ratio of lanthanum-modified bentonite to zirconium-modified zeolite is 1-2:1, more preferably 1.5:1. In this invention, when the sediment in the water body is high-phosphorus sediment with a total phosphorus content ≥2.0 mg / g, the preferred mass ratio of lanthanum-modified bentonite to zirconium-modified zeolite is 2:1; when the pH of the water body is >8.5, the preferred mass ratio of lanthanum-modified bentonite to zirconium-modified zeolite is 1:1.
[0029] In this invention, the sediment passivation-targeted adsorption layer is the basic functional layer of the "photo-biological-adsorption" three-layer composite system. It can reduce the release of endogenous pollutants from the sediment into the overlying water and form a synergistic pollution control system with the upper functional units. At the same time, it physically blocks the upward diffusion of reducing substances from the sediment. The sediment passivation-targeted adsorption layer can adsorb and fix nitrogen and phosphorus pollutants and some heavy metals released from the sediment, and block the diffusion of reducing substances from the sediment into the overlying water. The upper photocatalytic and biological fixation units can reduce the organic pollutant load in the overlying water and their competitive occupation of the bottom adsorption sites, thereby helping to maintain the long-term pollution control performance of the bottom layer.
[0030] In this invention, the skeleton support material preferably includes one or more of quartz sand, volcanic rock particles, shale ceramsite, and zeolite coarse aggregate. The particle size of the skeleton support material is preferably 0.5-5 mm, more preferably 1-3 mm. The mass of the skeleton support material is preferably 10-15% of the mass of the mineral adsorbent material, more preferably 12-14%. In this invention, the sediment passivation-targeted adsorption layer also preferably includes one or more of iron oxide, manganese oxide, and hydroxyapatite. The iron oxide is preferably iron(II,III) oxide or iron(III) oxide, with a particle size preferably ≥100 mesh, more preferably 100-200 mesh; the manganese oxide is preferably manganese dioxide, with a particle size preferably ≥100 mesh, more preferably 100-200 mesh; and the hydroxyapatite has a particle size preferably ≥200 mesh, more preferably 200-300 mesh. This invention enhances the adsorption capacity for heavy metals such as cadmium and lead by adding iron oxide, manganese oxide, or hydroxyapatite. In this invention, the mass content of the iron oxide, manganese oxide or hydroxyapatite in the sediment passivation-targeted adsorption layer is preferably 2-8%, more preferably 4-6%.
[0031] In this invention, the middle layer of the composite water purification material is a cross-linked modified biological carrier layer, comprising a cross-linked modified porous biological carrier and low-temperature functional bacteria immobilized within the porous biological carrier. In this invention, the porous biological carrier preferably comprises one or more of polyurethane sponge, polypropylene fiber, activated carbon fiber, ceramsite, and porous ceramics; when the porous biological carrier is granular, its particle size is preferably 2-3 mm; when the porous biological carrier is fibrous, its fiber diameter is preferably 0.1-0.5 mm, and its length is preferably 2-5 mm. In this invention, the pore size of the porous biological carrier is preferably 25-35 μm, the porosity is preferably ≥85%, and the specific surface area is preferably ≥145 m². 2 / g. In this invention, the porous biological carrier is preferably a hydrophilic-hydrophobic balanced modified porous biological carrier, and its water contact angle is preferably 63~67°, more preferably 65°.
[0032] In this invention, the method for preparing the crosslinked modified porous biocarrier includes the following steps: The porous biological carrier is pre-activated by argon plasma to obtain a surface-activated biological carrier; the surface-activated biological carrier is placed in a treatment solution containing an amination reagent for amination treatment to form an amino functional layer on the surface of the biological carrier to obtain an amination biological carrier; the amination biological carrier is immersed in glutaraldehyde solution for cross-linking treatment to form aldehyde active sites on the carrier surface to obtain a cross-linked modified porous biological carrier.
[0033] Before the argon plasma surface activation modification, the porous biological carrier is preferably pretreated. The pretreatment method preferably includes the following steps: placing the porous biological carrier in ethanol, performing ultrasonic cleaning, water washing, and drying. In this invention, the ultrasonic cleaning power is preferably 80W, and the time is preferably 20 minutes. Through ultrasonic cleaning, this invention removes surface oil, additives, and impurities.
[0034] In this invention, the pretreated porous biological carrier is preferably laid flat in a plasma treatment chamber with a thickness ≤5mm, and then subjected to argon plasma surface activation modification. The preferred parameters for the argon plasma surface activation modification include: discharge power preferably 80~120W, more preferably 100W; chamber pressure preferably 15~25Pa, more preferably 20Pa; and treatment time preferably 3~8min, more preferably 5min. This invention first pre-activates the carrier surface with argon plasma, then grafts an amino functional layer onto the carrier surface using an amination reagent, increasing the surface roughness and achieving a water contact angle of 63°~67°, more preferably 65°, which is beneficial for improving the colonization stability and activity retention of low-temperature functional bacteria. The modified carrier is sealed and stored at 4℃, and the subsequent cross-linking and fixation process is completed within 24 hours.
[0035] This invention involves mixing the surface-activated biological carrier with a grafting solution containing an amination reagent to perform an amination reaction, thereby obtaining an amination biological carrier. In this invention, the amination reagent in the grafting solution preferably includes one or more of aminopropyltriethoxysilane, aminopropyltrimethoxysilane, chitosan, and polyethyleneimine. When the amination reagent is aminopropyltriethoxysilane or aminopropyltrimethoxysilane, the mass fraction of the amination reagent in the grafting solution is 0.5-3.0%, more preferably 1.0-2.0%; the solvent is ethanol, water, or an ethanol-water mixture; the grafting temperature is preferably 20-40°C, more preferably 30°C; and the grafting time is preferably 0.5-4 hours, more preferably 1-3 hours.
[0036] This invention involves immersing the aminated biological carrier in a glutaraldehyde solution for cross-linking treatment, thereby forming aldehyde-active sites on the carrier surface. The cross-linked modified biological carrier is then mixed and incubated with low-temperature acclimation functional bacteria. Free bacterial cells are washed away, and residual aldehyde groups are blocked, resulting in a porous biological carrier loaded with low-temperature functional bacteria. In this invention, the mass concentration of the glutaraldehyde solution is preferably 0.1%~0.5%, more preferably 0.3%, the cross-linking reaction temperature is preferably 2~8℃, more preferably 4℃, and the reaction time is preferably 0.5~2h, more preferably 1h. In this invention, the aldehyde-active sites can undergo cross-linking reactions with amino groups on the surface of microbial cells, thereby improving the immobilization stability of low-temperature functional bacteria on the porous biological carrier surface.
[0037] In this invention, the low-temperature functional bacteria include one or more of cold-resistant nitrifying bacteria, cold-resistant denitrifying bacteria, and low-temperature phosphate-solubilizing bacteria. As a specific embodiment of this invention, the low-temperature functional bacteria are preferably a compound strain. The cold-resistant nitrifying bacteria are selected from *Nitrosomonas* and *Nitrobacterium*, the cold-resistant denitrifying bacteria are selected from *Pseudomonas* and *Bacillus*, and the low-temperature phosphate-solubilizing bacteria are selected from *Bacillus megaterium* and *Burkholderia*. The ratio of viable bacteria is preferably (2~3):(2~3):(0.8~1.2), more preferably 2:2:1. In this invention, the low-temperature functional bacteria are preferably sourced from the surface sediment of naturally frozen water bodies at 0~2℃ during winter. They are obtained through initial enrichment using a low-temperature selective culture medium and purification by streak plating at low temperatures. In this invention, the culture medium ratio and dissolved oxygen conditions are maintained throughout the low-temperature acclimatization process. In this invention, the low-temperature selective culture medium used includes nitrifying bacteria culture medium, denitrifying bacteria culture medium, and phosphate-solubilizing bacteria culture medium. The preferred basic components of the nitrifying bacteria culture medium are: 2.85 g trisodium citrate, 1.18 g (NH4)2SO4, 0.8 g K2HPO4, 0.4 g KH2PO4, and 0.2 g MgSO4·7H2O. The preferred basic components of the denitrifying bacteria culture medium are: 2.85 g trisodium citrate, 1.81 g KNO3, 0.8 g K2HPO4, 0.4 g KH2PO4, and 0.2 g MgSO4·7H2O. The preferred basic components of the phosphate-solubilizing bacteria culture medium are: 3.68 g sodium acetate, 0.029 g Na2HPO4, 0.057 g NH4Cl, 0.017 mol / L CaCl2, 0.13 g MgSO4, 0.027 g K2SO4, and 12 g HEPES. All the above culture media were supplemented with 0.5 mL of concentrated trace element solution (FeSO4·7H2O 5g, EDTA 50g, ZnSO4·7H2O 4.32g, H3BO3 11g, MnSO4·H2O 4.32g, CoCl2·6H2O 1.61g, CuSO4·5H2O 1.57g, (NH4)Mo 7O). 24 Add 1.1g of 4H2O, add distilled water to 1L, adjust the pH to 6.5 using KOH granules, add distilled water to 1L, pH=7.0~7.2, and sterilize in a vertical pressure sterilizer for 20~30min after preparation.
[0038] In this invention, the cryogenic functional bacteria are cryogenically acclimatized bacteria. The cryogenic acclimatization preferably includes: culturing a suspension of the cryogenic functional bacteria at 15°C for 5-10 days, more preferably 7 days; culturing at 10°C for 5-10 days, more preferably 7 days; and culturing at 5°C for 10-20 days, more preferably 14 days. The cryogenically acclimatized bacteria exhibit a specific growth rate ≥0.051 h⁻¹ at 5°C. -1 This invention preferably involves differentiated control of dissolved oxygen conditions during the low-temperature acclimatization stage. Specifically, the dissolved oxygen in the nitrifying bacteria culture system is maintained at 5-7 mg / L; the dissolved oxygen in the denitrifying bacteria culture system is controlled at 0.5-2 mg / L; and the dissolved oxygen in the phosphate-solubilizing bacteria culture system is maintained at 3-5 mg / L. Through the aforementioned low-temperature acclimatization and immobilization treatment, this invention improves the survival stability and pollutant transformation capacity of low-temperature functional bacteria in low-temperature water bodies, enabling them to participate in the degradation of organic pollutants, nitrogen transformation, and / or phosphorus removal at 5-10℃. At 0-5℃, the low-temperature functional bacteria serve as an auxiliary unit for the pollution control function of the composite material.
[0039] In this invention, the surface layer is a low-temperature responsive photocatalytic layer, comprising a visible light responsive composite semiconductor photocatalyst, and preferably a binder. In this invention, the visible light responsive composite semiconductor photocatalyst preferably comprises one of a g-C3N4 / BiVO4 composite catalyst, a g-C3N4 / Bi2WO6 composite catalyst, a TiO2 / BiVO4 composite catalyst, and a g-C3N4 / ZnO composite catalyst, more preferably a g-C3N4 / BiVO4 composite catalyst. In this invention, the mass of g-C3N4 is preferably 1-15% of the total mass of the g-C3N4 / BiVO4 composite catalyst, more preferably 5-10%. In this invention, the preparation method of the g-C3N4 / BiVO4 composite catalyst preferably includes the following steps: Bismuth trichloride, hexadecyltrimethylammonium bromide and ethylene glycol were mixed and sodium vanadate dodecahydrate was added to carry out a hydrothermal reaction to obtain BiVO4 nanosheets; Melamine was calcined to obtain blocky g-C3N4 particles. The blocky g-C3N4 particles were mixed with a mixed acid solution for acid modification. The resulting acid-modified product was mixed with water and allowed to stand for aging to obtain acid-modified g-C3N4 nanoparticles. A mixture of BiVO4 nanosheet aqueous suspension and acidified modified g-C3N4 nanoparticle aqueous dispersion was subjected to ultrasonication and stirring to obtain g-C3N4 / BiVO4 composite catalyst.
[0040] This invention involves mixing bismuth trichloride, hexadecyltrimethylammonium bromide, and ethylene glycol, then adding sodium vanadate dodecahydrate, and conducting a hydrothermal reaction to obtain BiVO4 nanosheets. In this invention, the preferred molar ratio of bismuth trichloride to hexadecyltrimethylammonium bromide is 0.005~0.02:0.002~0.01; the preferred molar ratio of sodium vanadate dodecahydrate to bismuth trichloride is 1:1. In this invention, the preferred mixing time for bismuth trichloride, hexadecyltrimethylammonium bromide, and ethylene glycol is 30~50 min, and after adding sodium vanadate dodecahydrate, mixing is preferably continued for another 30~50 min.
[0041] In this invention, the hydrothermal reaction temperature is preferably 110-130℃, more preferably 120℃, and the reaction time is preferably 10-14h, more preferably 11-12h. After the hydrothermal reaction, the product is preferably cooled to room temperature for solid-liquid separation, washing, drying, and grinding. In this invention, the washing reagent is preferably a 7:3 volume ratio deionized water-anhydrous ethanol mixture, and the washing is preferably performed 3-5 times; the drying temperature is preferably 60-100℃, and the drying time is preferably 6-12h. In this invention, the BiVO4 nanosheets have a preferred diameter of 400-500nm and a preferred thickness of 10-40nm.
[0042] This invention involves calcining melamine to obtain blocky g-C3N4 particles. These particles are then mixed with a mixed acid solution for acid modification. The resulting acid-modified product is mixed with water and allowed to stand for aging to obtain acid-modified g-C3N4 nanoparticles. In this invention, the calcination of the melamine is preferably carried out in a nitrogen atmosphere. The calcination temperature is preferably 550-650℃, more preferably 600℃, and the holding time is preferably 2-4 hours, more preferably 3 hours. The heating rate to the calcination temperature is preferably 2-5℃ / min. After calcination, the product is preferably naturally cooled to room temperature. The uncalcined surface material is removed, and the internal pale yellow solid is ground. In this invention, the mixed acid solution is preferably a mixture of concentrated nitric acid (65-68 wt%) and concentrated sulfuric acid (95-98 wt%), with the volume ratio of concentrated nitric acid to concentrated sulfuric acid preferably being 1:1. In this invention, the acidification modification temperature is preferably 70-90℃, more preferably 80℃, and the time is preferably 2-6 hours, more preferably 3-5 hours. In this invention, the static aging temperature is preferably room temperature, and the time is preferably 5-10 hours, more preferably 6-8 hours. After static aging, a white precipitate precipitates. In this invention, the precipitate is preferably filtered, washed, dried, and ground. In this invention, the washing reagent is preferably deionized water and anhydrous ethanol, and the drying temperature is preferably 60-80℃. In this invention, the particle size of the acidified g-C3N4 nanoparticles is preferably 40-60 nm.
[0043] This invention involves mixing an aqueous suspension of BiVO4 nanosheets with an acid-modified aqueous dispersion of g-C3N4 nanoparticles, followed by ultrasonication and stirring to obtain a g-C3N4 / BiVO4 composite catalyst. In this invention, the ultrasonic power is preferably 150-250 W, more preferably 200 W, and the time is preferably 20-40 min, more preferably 30 min. The stirring rate is preferably 150-250 rpm, more preferably 200 rpm, and the stirring time is preferably 12-36 h, more preferably 20-30 h. After stirring, the resulting precipitate system is preferably filtered, washed, dried, and ground. The washing reagents are preferably deionized water and anhydrous ethanol, and the drying temperature is preferably 60-80℃. In this invention, g-C3N4 particles are uniformly loaded on the surface of BiVO4 nanosheets.
[0044] In this invention, the adhesive preferably includes one or more of water-based acrylic adhesive, water-based polyurethane adhesive, and silica sol; the mass of the adhesive is preferably 5-8% of the mass of the visible light responsive composite semiconductor photocatalyst, more preferably 6-7%.
[0045] In this invention, the overall thickness of the photocatalytic-biological immobilization-sediment adsorption composite water purification material is preferably 15-30 mm, more preferably 20-25 mm; the thickness of the bottom layer is preferably 8-15 mm, more preferably 10-12 mm; the thickness of the middle layer is preferably 5-10 mm, more preferably 6-8 mm; and the thickness of the surface layer is preferably 2-5 mm, more preferably 3-4 mm. The layers are preferably separated by non-woven fabric and fixed using a needle-punching composite process. The non-woven fabric is preferably made of polyester fiber (PET) or polypropylene fiber (PP), and its thickness is preferably 0.3-0.8 mm, more preferably 0.5-0.6 mm. In this invention, the photocatalytic-biological immobilization-sediment adsorption composite water purification material is preferably prepared as a sheet, plate, or block-shaped oriented composite material. During use, the sediment passivation-targeted adsorption layer is in contact with the sediment surface, and the low-temperature responsive photocatalytic layer faces the overlying water and light direction to achieve a synergistic effect of reducing water pollutants and controlling endogenous pollution in the sediment.
[0046] Preferably, the size of a single piece of the composite material is 500mm×500mm~1000mm×1000mm; adjacent composite materials can be spliced and laid, and fixed to the bottom mud surface by ballast, anchoring, edge fixing or net bag limiting.
[0047] As a specific embodiment of the present invention, the structural schematic diagram of the photocatalytic-biological immobilization-sediment adsorption composite water purification material is shown below. Figure 1 As shown.
[0048] This invention provides a method for preparing the above-mentioned photocatalytic-biological immobilization-sediment adsorption composite water purification material, comprising the following steps: (1) Mix mineral adsorbent material modified with rare earth elements and / or transition metal elements, skeleton support material and inorganic binder, press and solidify them to obtain sediment passivation-targeted adsorption layer. (2) The porous biological carrier is subjected to argon plasma surface pre-activation treatment to obtain a surface-activated biological carrier; the surface-activated biological carrier is mixed with a grafting solution containing an amination reagent and subjected to an amination reaction to obtain an amination biological carrier; the amination biological carrier is immersed in glutaraldehyde solution and subjected to cross-linking treatment to obtain a cross-linked modified porous biological carrier. The low-temperature functional strains were subjected to low-temperature acclimatization to obtain low-temperature acclimatized functional bacteria; the cross-linked modified porous biological carrier was mixed and incubated with the low-temperature acclimatized functional bacteria, and the unfixed free bacterial cells were washed away and the residual aldehyde groups were blocked to obtain a porous biological carrier loaded with low-temperature functional bacteria; the porous biological carrier loaded with low-temperature functional bacteria was fixed on the surface of the sediment passivation-targeted adsorption layer to obtain a cross-linked modified biological carrier layer. (3) The visible light responsive composite semiconductor photocatalyst is mixed with a binder and coated on the surface of the cross-linked modified biological carrier layer to obtain a low-temperature responsive photocatalytic layer; (4) The sediment passivation-targeted adsorption layer, the cross-linked modified biological carrier layer and the low-temperature responsive photocatalytic layer are sequentially composited and fixed from bottom to top to obtain a photocatalytic-biological fixation-sediment adsorption composite water purification material.
[0049] This invention mixes a mineral adsorbent material modified with rare earth elements and / or transition metal elements, a framework support material, and an inorganic binder, then performs compression molding and curing to obtain a sediment passivation-targeted adsorption layer. In this invention, the mineral adsorbent material modified with rare earth elements and / or transition metal elements preferably includes lanthanum-modified bentonite and zirconium-modified zeolite. The preparation methods of the lanthanum-modified bentonite and zirconium-modified zeolite are the same as described above and will not be repeated here. In this invention, the compression molding pressure is preferably 5~10 MPa, more preferably 6~8 MPa, and the molding time is preferably 20~40 s, more preferably 30 s. The density of the sediment passivation-targeted adsorption layer after compression molding is preferably 0.8~1.2 g / cm³. 3 More preferably 0.9~1g / cm 3 .
[0050] In this invention, the preparation methods for the cross-linked modified biological carrier layer and the low-temperature acclimatization functional bacteria are the same as described above and will not be repeated here. In this invention, the mixed incubation is preferably carried out under shaking conditions. During the incubation, the OD of the low-temperature acclimatization functional bacteria... 600The preferred concentration is 0.5~0.7, more preferably 0.6; the preferred incubation temperature is 2~8℃, more preferably 4℃; and the preferred incubation time is 2~5h, more preferably 3h. This invention improves the immobilization stability of low-temperature functional bacteria on the carrier surface and within the pores through the mixed incubation, aided by surface amination and glutaraldehyde cross-linking. After the mixed incubation, the unfixed free bacterial cells are washed away, and residual aldehyde groups are blocked using a buffer solution containing an amino blocking agent. In this invention, the amino blocking agent in the buffer solution preferably includes one or more of glycine, ethanolamine, and lysine.
[0051] This invention fixes the porous biological carrier loaded with low-temperature functional bacteria onto the surface of a sediment passivation-targeted adsorption layer, resulting in a cross-linked modified biological carrier layer. In this invention, the fixation method is preferably to fix the porous biological carrier loaded with low-temperature functional bacteria between two layers of nonwoven fabric using an adhesive. In this invention, the adhesive is preferably one or more of water-based acrylic adhesives, water-based polyurethane adhesives, and silica sol.
[0052] In this invention, the method for preparing the low-temperature responsive photocatalytic layer includes the following steps: A visible light responsive composite semiconductor photocatalyst was mixed with a binder and coated onto the surface of a cross-linked modified biological carrier layer to obtain a low-temperature responsive photocatalytic layer.
[0053] In this invention, the mass of the binder is preferably 5-8% of the mass of the visible light responsive composite semiconductor photocatalyst, more preferably 6-7%, and the binder preferably includes one or more of water-based acrylic binders, water-based polyurethane binders, and silica sol. After the visible light responsive composite semiconductor photocatalyst is mixed with the binder, the coating amount on the surface of the crosslinked modified biological carrier layer is preferably 150-250 g / m². 2 More preferably 180~220g / m 2 .
[0054] This invention involves sequentially composite and immobilize the sediment passivation-targeted adsorption layer, the cross-linked modified biological carrier layer, and the low-temperature responsive photocatalytic layer from bottom to top to obtain a photocatalytic-biological immobilization-sediment adsorption composite water purification material. In this invention, the layers are preferably separated by non-woven fabric and fixed using a needle-punching composite process to form an integrated sheet or block material. The size of a single sheet can be customized according to engineering requirements, specifically from 500mm×500mm to 1000mm×1000mm, facilitating on-site laying and splicing.
[0055] This invention provides the application of the aforementioned photocatalytic-biological immobilization-sediment adsorption composite water purification material in low-temperature water treatment, wherein the temperature of the water body during the low-temperature period is 0~10℃. As a specific embodiment of this invention, the water quality parameters of the water body include: COD 50~200 mg / L, ammonia nitrogen 5~30 mg / L, total nitrogen 10~40 mg / L, and total phosphorus 0.2~3.0 mg / L.
[0056] The following detailed description, in conjunction with embodiments, illustrates the photocatalytic-biological immobilization-sediment adsorption composite water purification material, its preparation method, and its application, but these should not be construed as limiting the scope of protection of this invention.
[0057] Example 1 Sediment passivation - preparation of targeted adsorption layer: (1) Preparation of Lanthanum-Modified Bentonite Powder Weigh 40g of sodium-based bentonite and add it to 1000mL of 10% sulfuric acid solution. Stir at 200rpm for 1h at room temperature for acidification and activation. After activation, wash the material with deionized water until the pH of the filtrate is 7. After soaking for 24h, filter to separate the solid. Place the filter cake in an 80℃ forced-air drying oven for 6h. After grinding and passing through a 100-mesh standard sieve, acidified bentonite is obtained.
[0058] Weigh 3.1 g of the above-mentioned acidified bentonite and add it to 200 mL of deionized water. Stir to form a stable suspension. Add lanthanum chloride heptahydrate to adjust the lanthanum ion concentration in the system to 59.95 mmol / L. After ultrasonic dispersion at 200 W for 30 min at room temperature, place the suspension in a 50℃ constant temperature water bath and stir at 200 rpm for 2.4 h. Then, slowly add 1 mol / L sodium carbonate solution and stir vigorously until the pH of the system stabilizes at 8.0 ± 0.2. Continue stirring for 2 h to allow the lanthanum component to be stably loaded on the surface and between layers of the bentonite.
[0059] After the reaction, the solid was separated by filtration. The filter cake was washed four times with deionized water until no white precipitate was formed upon addition of silver nitrate solution. The washed filter cake was dried in an 80°C forced-air drying oven for 6 hours, ground through a 100-mesh standard sieve, and sealed for storage to obtain lanthanum-modified bentonite powder.
[0060] (2) Preparation of zircon-modified zeolite: Weigh 100g of natural zeolite and add it to 250mL of deionized water. Stir magnetically for 30min to form a homogeneous suspension. Add 20g of zirconium oxychloride octahydrate and continue stirring until completely dissolved. Slowly add 2mol / L sodium hydroxide solution at a dropping rate of 5mL / min to adjust the pH of the mixture to 10.0±0.2, stirring constantly throughout the process. After reacting at room temperature for 2h, perform solid-liquid separation. Wash the solid with deionized water until the pH of the supernatant stabilizes at around 7.0. Dry the solid in a 105℃ forced-air drying oven for 12h, crush it, and pass it through a 100-mesh standard sieve to obtain zircon-modified zeolite powder.
[0061] (3) Lanthanum-zirconium composite passivating agent The prepared lanthanum-modified bentonite powder and zirconium-modified zeolite powder were added to a dry powder mixer at a dry basis mass ratio of 3:2 and mixed at 150 rpm for 20 min to obtain the lanthanum-zirconium composite passivating agent (LMB-Zr-Z).
[0062] Example 2 Preparation of porous biocarrier particles loaded with low-temperature functional bacteria: Select uniformly sized open-cell polyurethane foam (pore size 25~35μm, porosity ≥85%, specific surface area ≥145m²). 2 / g), cut into carrier particles with a particle size of 2~3mm. The cut carrier particles are placed in anhydrous ethanol and ultrasonically cleaned at 80W power for 20min to remove surface oil, additives and impurities. Then rinsed with deionized water until the cleaning solution is neutral, dried in an oven at 60℃ to constant weight, cooled and sealed for later use.
[0063] Pretreated carrier particles were spread evenly in a plasma treatment chamber with a thickness ≤5 mm. Surface activation modification was performed using argon plasma with the following parameters: discharge power 100 W, chamber pressure 20 Pa, and constant temperature treatment for 5 min. The modified carrier surface roughness was improved, forming active sites conducive to subsequent grafting. The water contact angle remained stable at 65°±2°, which is beneficial for improving the colonization stability and activity retention of low-temperature functional bacteria. The argon plasma-activated carrier particles were then immersed in a 1.0% (w / w) aminopropyltriethoxysilane ethanol-water mixed solution (ethanol to water volume ratio 9:1) at 25°C for 2 h. After the reaction, the particles were washed sequentially with ethanol and deionized water to remove ungrafted aminosilane, and then dried at 60°C for 2 h to obtain biological carrier particles with an amino functional layer on the surface.
[0064] The aminated biological carrier particles were sterilized by ultraviolet light for 30 min, then immersed in a 0.3% glutaraldehyde solution and crosslinked at 4°C for 1 h. After crosslinking, the particles were washed 5 times with pre-cooled deionized water at 4°C to obtain crosslinked modified carrier particles with aldehyde active sites on the surface.
[0065] The surface sediment of naturally frozen water bodies in winter (0-2℃) was selected as the bacterial source and stored in a sealed, light-protected environment. Native cold-resistant nitrifying bacteria, cold-resistant denitrifying bacteria, and cold-resistant phosphate-solubilizing bacteria were obtained through initial enrichment on a low-temperature selective culture medium and purification by streak plating on low-temperature solid plates. The purified strains were mixed in a 2:2:1 ratio to prepare a compound bacterial suspension, which underwent directional low-temperature acclimatization using a gradient cooling method: 7 days of shaking enrichment culture at 15℃, 7 days of transitional acclimatization culture at 10℃, and 14 days of directional low-temperature acclimatization culture at 5℃, with stable culture medium ratios and dissolved oxygen conditions throughout. After acclimatization, the compound bacterial agent exhibited a specific growth rate ≥0.051 h at 5℃. -1 It possesses the ability to participate in nitrogen conversion, phosphorus removal, and organic matter degradation under conditions of 5-10℃. The cross-linked carrier particles are then incorporated into the OD... 600 In a 0.6% low-temperature acclimation compound bacterial agent system, the microorganisms were incubated at 4°C and 100 rpm for 3 hours to allow them to attach and immobilize on the carrier surface and within the pores. After incubation, the microorganisms were washed with sterile physiological saline or sterile buffer to remove unfixed free bacteria. The washed carrier particles were then placed in phosphate buffer containing 50 mmol / L glycine and blocked at 4°C for 30 minutes to block residual aldehyde groups. Subsequently, the particles were washed with sterile physiological saline to obtain porous biological carrier particles loaded with low-temperature functional bacteria.
[0066] Example 3 Preparation of low-temperature responsive g-C3N4 / BiVO4 photocatalytic layer (1) Preparation of BiVO4 nanosheets 2.21 g of bismuth trichloride (BiCl3) and 1.05 g of hexadecyltrimethylammonium bromide (CTAB) were added to 80 mL of ethylene glycol and stirred for 40 min to obtain a homogeneous mixed solution. An equimolar amount of sodium vanadate dodecahydrate (Na3VO4·12H2O) equal to that of BiCl3 was dissolved in 6 mL of deionized water. After stirring to dissolve, the solution was slowly added dropwise to the above ethylene glycol mixed solution. After the addition was complete, stirring was continued for 40 min.
[0067] The mixture was transferred to a polytetrafluoroethylene-lined high-pressure reactor and hydrothermally reacted at 120°C for 12 hours. After the reaction, it was allowed to cool naturally to room temperature. The yellow precipitate was collected and filtered. It was washed 3-5 times with a 7:3 volume ratio of deionized water to anhydrous ethanol to remove residual additives and solvents. The washed precipitate was dried at 80°C for 10 hours and then ground to obtain BiVO4 nanosheets.
[0068] (2) Preparation of g-C3N4 nanoparticles 20g of melamine was placed in an alumina crucible and then placed in a muffle furnace. The temperature was increased to 600℃ at a rate of 3℃ / min and calcined for 3 hours. The mixture was then allowed to cool naturally to room temperature. The incompletely calcined surface material was removed, and the pale yellow solid inside was ground to obtain blocky g-C3N4 particles.
[0069] Blocky g-C3N4 particles were dispersed in a 1:1 volume ratio mixed acid solution of concentrated nitric acid (65-68 wt%) and concentrated sulfuric acid (95-98 wt%), and stirred in a constant temperature water bath at 80°C for 5 hours until the solution became clear. The mixture was slowly diluted with a large amount of deionized water and allowed to stand for 8 hours, resulting in the precipitation of a white precipitate. The precipitate was filtered, washed with deionized water and anhydrous ethanol until the filtrate was neutral, dried at 80°C, and then ground to obtain acid-modified g-C3N4 nanoparticles.
[0070] (3) Constructing g-C3N4 / BiVO4 visible light responsive composite semiconductor 0.95 g of BiVO4 nanosheets were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 min followed by magnetic stirring for 30 min to obtain a uniform BiVO4 suspension. 0.05 g of acidified modified g-C3N4 nanoparticles were dispersed in 100 mL of deionized water and the same ultrasonic and stirring process was used to obtain a g-C3N4 dispersion.
[0071] According to the ratio of g-C3N4 nanoparticles to 5% of the total mass of the composite material, the corresponding volume of g-C3N4 dispersion was slowly added dropwise to the BiVO4 suspension. After the addition was completed, the mixture was sonicated for 30 min and then magnetically stirred for 24 h. The precipitate was filtered, washed three times with deionized water and three times with anhydrous ethanol, dried at 80 °C, and then ground to obtain the g-C3N4 / BiVO4 visible light responsive composite semiconductor composite material.
[0072] Example 4 Overall preparation of photocatalysis-biological immobilization-sediment adsorption composite water purification material: Sediment passivation-targeted adsorption layer: 12 mm thick, using the lanthanum-zirconium composite passivator (LMB-Zr-Z) prepared in Example 1 as the main functional component, adding 12% by mass of lanthanum-zirconium composite passivator in quartz sand as the skeleton support material, and adding 5% by mass of the lanthanum-zirconium composite passivator in silica sol as an inorganic binder; after uniform mixing, it is pressed into shape under 10 MPa pressure, held for 30 s, and cured at 60℃ for 12 h to obtain a density of 1.0 g / cm³. 3 Substrate passivation-targeted adsorption layer.
[0073] Cross-linked modified biological carrier layer: 8 mm thick, using porous biological carrier particles loaded with low-temperature functional bacteria prepared in Example 2, with a particle size of 2-3 mm, fixed on a non-woven fabric substrate by an adhesive, with a carrier filling rate of 90%.
[0074] Low-temperature responsive g-C3N4 / BiVO4 photocatalytic layer: 3 mm thick, the g-C3N4 / BiVO4 visible light responsive composite semiconductor material prepared in Example 3 is mixed with 6% by mass of water-based acrylic binder and uniformly coated onto the surface of the biological carrier layer, with a coating amount of 200 g / m². 2 .
[0075] The layers are separated by non-woven fabric and fixed by needle punching composite process to form an integrated sheet material with a single sheet size of 1000mm×1000mm.
[0076] Test Example 1 A laboratory-simulated water-sludge static reaction system was used, with an effective reactor volume of 5L, a bottom sediment layer thickness of 10cm, and a water depth of 30cm. The experimental water was artificially prepared simulated polluted water with the following initial qualities: COD 140mg / L, ammonia nitrogen 15mg / L, total nitrogen 20mg / L, and total phosphorus 1.0mg / L. The bottom sediment was taken from a northern winter riverbed, with a total phosphorus content of 1.7mg / g and an organic matter content of 8.0%.
[0077] Three low-temperature gradients (0℃, 5℃, and 10℃) were set up, and a constant-temperature incubator was used for precise temperature control; the light source was simulated visible light with a light intensity of 300 W / m². 2 The material receives 12 hours of sunlight daily. It is applied to the bottom mud surface in a full-coverage manner, with a total dry weight of 13 kg / m². 2 The areal density of the sediment passivation-targeted adsorption layer is 12.0 kg / m³. 2 The total areal density of the cross-linked modified biological carrier layer, the low-temperature responsive photocatalytic layer, the non-woven fabric isolation layer, and the binder component is 1.0 kg / m³. 2 A blank control group was set up simultaneously, which was a water-cement system without the addition of purification materials. Each experiment had 3 parallel samples.
[0078] The removal rate of each pollutant is calculated according to the following formula 1: Formula 1; In formula 1: R net —Net removal rate of pollutants, % C 0 —— The initial concentration of the corresponding pollutant in the overlying water at the start of the experiment, in mg / L; Cb —— The corresponding pollutant concentration in the overlying water at time t in the blank control group (mg / L); C t —— The experimental group that added the composite material of the present invention had the corresponding pollutant concentration in the supernatant water at time t, in mg / L.
[0079] The net removal rate is used to reflect the net contribution of the composite material to the change in pollutant concentration compared with the blank control group; each group of experiments has no less than 3 parallel samples, and the results are expressed as mean ± standard deviation.
[0080] Overlying water samples were collected after 7, 14, and 28 days of continuous operation to determine the concentrations of COD, ammonia nitrogen, total nitrogen, and total phosphorus. Each experiment had three replicates, and the results are expressed as mean ± standard deviation. One-way ANOVA was used to compare the differences between each experimental group and the blank control group, as well as between each comparative group. A p-value < 0.05 was considered statistically significant. The net removal rates of each pollutant under different temperature and operating time conditions are shown in Table 1. Table 1. Average removal rates of various pollutants in water by the material under different temperatures and operating times.
[0081] Comparative Example To verify the technical advantages of this invention, the following comparative examples are provided: Comparative Example 1: Conventional photo-biological coupling system. Nano-TiO2 was used as the photocatalyst component. A polyurethane sponge without argon plasma surface pre-activation, amylation grafting, or glutaraldehyde cross-linking was used as the biological carrier. Functional bacteria without low-temperature acclimation were loaded onto the carrier, and no sediment passivation-targeted adsorption layer was provided. The photocatalyst coating amount was 200 g / m³. 2 The thickness of the biological carrier layer was 10 mm; the remaining experimental conditions were the same as in Example 4.
[0082] Comparative Example 2: Sediment passivation-targeted adsorption layer omitted. Only the biological carrier layer and the low-temperature responsive g-C3N4 / BiVO4 photocatalytic layer are retained, and the sediment passivation-targeted adsorption layer is not set; the remaining material composition, layer thickness, preparation conditions and experimental conditions are the same as in Example 4.
[0083] Comparative Example 3: Unacclimated bacterial group. The low-temperature acclimation compound bacterial agent loaded in Example 4 was replaced with the same bacterial species combination that had not undergone gradient cooling acclimation; the biological carrier particles were still subjected to the same surface activation and cross-linking-assisted immobilization treatment; the remaining material composition, layer thickness, preparation conditions and experimental conditions were the same as in Example 4.
[0084] Comparative Example 4: The cross-linked modified biological carrier particles in Example 4 were replaced with polyurethane sponge particles of the same specifications that were not pre-activated by argon plasma, aminated grafting, or cross-linked with glutaraldehyde; the functional bacteria were still subjected to the same low-temperature acclimation treatment; the remaining material composition, layer thickness, preparation conditions, and test conditions were the same as in Example 4.
[0085] Comparative Example 5: Replacement of the underlying functional material group. The lanthanum-modified bentonite in the sediment passivation-targeted adsorption layer of Example 4 was replaced with unmodified bentonite, and the zircon-modified zeolite was replaced with natural zeolite; the type and amount of the framework support material, the thickness and density of the underlying layer were the same as in Example 4; the composition of other materials, preparation conditions and test conditions were the same as in Example 4.
[0086] Comparative Example 6: Replacement of photocatalytic layer material group. The g-C3N4 / BiVO4 composite photocatalyst of the low-temperature responsive photocatalytic layer in Example 4 was replaced with nano-TiO2, and the photocatalyst coating amount was 200 g / m. 2 The photocatalytic layer thickness is 3 mm; the composition of other materials, layer thickness, preparation conditions and experimental conditions are the same as in Example 4.
[0087] Under the same experimental conditions, at 10℃, with 12 hours of light per day and 14 days of operation, the net removal rates of COD, ammonia nitrogen, total nitrogen, and total phosphorus in Example 4 and each comparative example were measured; the results are expressed as mean ± standard deviation, and the specific results are shown in Table 2: Table 2. Net removal rates of COD, ammonia nitrogen, total nitrogen, and total phosphorus in Examples 4 and Comparative Examples 1-6
[0088] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A photocatalytic-biological immobilization-sediment adsorption composite water purification material, characterized in that, It includes a sediment passivation-targeted adsorption layer, a cross-linked modified biological carrier layer, and a low-temperature responsive photocatalytic layer arranged sequentially from bottom to top; the layers are fixedly connected by an isolation layer and / or an adhesive layer; The sediment passivation-targeted adsorption layer includes a mineral adsorption material and a framework support material, wherein the mineral adsorption material is modified with rare earth elements and / or transition metal elements. The cross-linked modified biological carrier layer includes a cross-linked modified porous biological carrier and low-temperature functional bacteria immobilized in the porous biological carrier; The low-temperature responsive photocatalytic layer includes a visible light responsive composite semiconductor photocatalyst. The sediment passivation-targeted adsorption layer is in contact with the sediment, and the low-temperature responsive photocatalytic layer is oriented towards the overlying water and light.
2. The photocatalytic-biological immobilization-sediment adsorption composite water purification material according to claim 1, characterized in that, The mineral adsorbent material includes lanthanum-modified bentonite and zirconium-modified zeolite, and the mass ratio of lanthanum-modified bentonite to zirconium-modified zeolite is 1~2:
1. The skeleton support material includes one or more of the following: quartz sand, volcanic rock particles, shale ceramsite, and zeolite coarse aggregate. The mass of the skeleton support material is 10-15% of the mass of the mineral adsorbent material.
3. The photocatalytic-biological immobilization-sediment adsorption composite water purification material according to claim 1 or 2, characterized in that, The sediment passivation-targeted adsorption layer also includes one or more of iron oxides, manganese oxides, and hydroxyapatite.
4. The photocatalytic-biological immobilization-sediment adsorption composite water purification material according to claim 1, characterized in that, The porous biocarrier includes one or more of polyurethane sponge, polypropylene fiber, activated carbon fiber, ceramsite, and porous ceramics; the porous biocarrier is granular or fibrous. The water contact angle of the porous biological carrier is 63~67°; The low-temperature functional bacteria include one or more of the following: cold-resistant nitrifying bacteria, cold-resistant denitrifying bacteria, and low-temperature phosphate-solubilizing bacteria.
5. The photocatalytic-biological immobilization-sediment adsorption composite water purification material according to claim 1, characterized in that, The visible light responsive composite semiconductor photocatalyst includes one of the following: g-C3N4 / BiVO4 composite catalyst, g-C3N4 / Bi2WO6 composite catalyst, TiO2 / BiVO4 composite catalyst, and g-C3N4 / ZnO composite catalyst.
6. The photocatalytic-biological immobilization-sediment adsorption composite water purification material according to claim 1, characterized in that, The thickness of the sediment passivation-targeted adsorption layer is 8~15mm, the thickness of the cross-linked modified biological carrier layer is 5~10mm, and the thickness of the low-temperature responsive photocatalytic layer is 2~5mm; the layers are separated by non-woven fabric and fixed by needle punching composite process.
7. The preparation method of the photocatalytic-biological immobilization-sediment adsorption composite water purification material according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Mix mineral adsorbent material modified with rare earth elements and / or transition metal elements, skeleton support material and inorganic binder, press and solidify them to obtain sediment passivation-targeted adsorption layer. (2) The porous biological carrier is subjected to argon plasma surface pre-activation treatment to obtain a surface-activated biological carrier; the surface-activated biological carrier is mixed with a grafting solution containing an amination reagent and subjected to an amination reaction to obtain an amination biological carrier; the amination biological carrier is immersed in glutaraldehyde solution and subjected to cross-linking treatment to obtain a cross-linked modified porous biological carrier. The low-temperature functional strains were subjected to low-temperature acclimatization to obtain low-temperature acclimatized functional bacteria; the cross-linked modified porous biological carrier was mixed and incubated with the low-temperature acclimatized functional bacteria, and the unfixed free bacterial cells were washed away and the residual aldehyde groups were blocked to obtain a porous biological carrier loaded with low-temperature functional bacteria; the porous biological carrier loaded with low-temperature functional bacteria was fixed on the surface of the sediment passivation-targeted adsorption layer to obtain a cross-linked modified biological carrier layer. (3) The visible light responsive composite semiconductor photocatalyst is mixed with a binder and coated on the surface of the cross-linked modified biological carrier layer to obtain a low-temperature responsive photocatalytic layer; (4) The sediment passivation-targeted adsorption layer, the cross-linked modified biological carrier layer and the low-temperature responsive photocatalytic layer are sequentially composited and fixed from bottom to top to obtain a photocatalytic-biological fixation-sediment adsorption composite water purification material.
8. The preparation method according to claim 7, characterized in that, In step (2), the discharge power of the argon plasma surface pre-activation treatment is 80~120W, the chamber pressure is 15~25Pa, and the treatment time is 3~8min; The amination reagent in the grafting solution containing the amination reagent includes one or more of aminopropyltriethoxysilane, aminopropyltrimethoxysilane, chitosan, and polyethyleneimine. The glutaraldehyde solution has a mass fraction of 0.1% to 0.5%, the crosslinking treatment temperature is 2 to 8°C, and the crosslinking treatment time is 0.5 to 2 hours. The low-temperature acclimatization includes: sequentially culturing the low-temperature functional strain suspension at 15℃ for 5-10 days, at 10℃ for 5-10 days, and at 5℃ for 10-20 days; During the mixed incubation, the OD of the low-temperature acclimatization functional bacteria... 600 The incubation temperature is 2-8℃, the incubation time is 2-5h, and the shaking speed is 80-120rpm.
9. The preparation method according to claim 7, characterized in that, In step (1), the density of the sediment passivation-targeted adsorption layer after pressing and molding is 0.8~1.2 g / cm³. 3 ; In step (3), the mass of the binder is 5-8% of the mass of the visible light responsive composite semiconductor photocatalyst; after the visible light responsive composite semiconductor photocatalyst is mixed with the binder, the coating amount on the surface of the cross-linked modified biological carrier layer is 150-250 g / m². 2 .
10. The application of the photocatalytic-biological immobilization-sediment adsorption composite water purification material according to any one of claims 1 to 6, or the photocatalytic-biological immobilization-sediment adsorption composite water purification material prepared by the preparation method according to any one of claims 7 to 9, in the control of water pollution in low-temperature periods, characterized in that, The temperature of the water body during the low-temperature period is 0~10℃.
